SKINFLINT DATING - Schwarcz H.P.; Rink W.J. (My University, 2001)
When a piece of flint is broken to form an artifact, and then buried in sediment at a site, its outer surface is exposed to a higher beta-particle dose rate than is experienced by the interior of the flint. A layer about 2mm thick on each freshly broken surface receives an excess β-dose. The difference between the internal accumulated dose and that in the skin can be used to estimate the time elapsed since formation and burial of the artifact.